Evaluation of reduction estrogenic activity in the combined treatment of landfill leachate and sanitary sewage. (October 2018) - Pesci Pereira, Camila; da Conceição Pereira, Tainá; Gomes, Giselle; Quintaes, Bianca Ramalho; Bila, Daniele Maia; Campos, Juacyara Carbonelli
Highlights: Co-treatment of landfill leachate and domestic sewage was simulated in lab scale. The 2% and 5% of leachate/sewage mixtures were treated in biological reactors. The kinetics of biodegradation decreases linearly according to the increase of leachate. The Seropedica landfill leachate presented a high estrogenic potential. There was reduction of estrogenic activity after biologic treatment of mixture. Abstract: Combined treatment of urban solid waste leachate and domestic sewage has emerged in Brazil and worldwide as an alternative to minimize the difficulties of treating landfill leachate. Landfill leachate is a complex matrix of organic and inorganic substances, recalcitrant material and xenobiotic organic compounds that are considered to be highly toxic, as well as endocrine disrupting compounds (EDC) that contribute to increased estrogenic activity. Although combined treatment is feasible for removal of organic matter, ammonia and toxicity, the efficiency of the removal of estrogenic substance is poorly investigated. In this study, the activated sludge process in batch and continuous modes was used for the combined treatment of 2% and 5% leachate/sewage mixtures. Estrogenic activity was reduced in reactors in both batch and continuous modes. The activated sludge process achieved average reductions of the estradiol equivalent (EQ-E2) values in the combined treatment of 94.5, 60.8 and 66.4% for the sanitary sewage, 2% mixture leachate in sewage and 5% mixture leachate in sewage reactors, respectively, in batch mode. For continuous reactors, 86%, 72%, and 65% of reduction of EQ-E2were achieved for sanitary sewage, 2 and 5% mixture with sanitary sewage. As for EQ-E2, the increase in the concentration of leachate in the sewage mixture was detrimental to the removal of estrogenic compounds during the biological process. Therefore, a limit on the % leachate/sewage mixtures should be established to achieve efficiency in the combined treatment of leachate in a Wastewater Treatment Plant (WWTP).